We can do this in one shot by using the point slope form instead, y-y1=m (x-x1) and simply solve for y.

The slope, m, is 3

The (x1,y1) is (0,-6)

y-y1=m (x-x1)

y-(-6)=3 (x-0)

y+6=3×-0

y+6=3x

y=3x-6

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now